Consumer acceptance and willingness to pay for direct and indirect entomophagy. Issue 2 (23rd July 2021) - Giotis, Thomas; Drichoutis, Andreas C
Abstract: Over the last few years, the interest on alternative protein sources, such as edible insects, has been growing rapidly. However, Western consumers' acceptance of insects as a food source is very low, mainly due to unfamiliarity with insect-based food. We investigate consumers' attitude and behavior and estimate their willingness to pay (WTP) a premium for three products that vary on a between-subjects basis, direct or indirect consumption of insects. The data were collected through an online questionnaire of 451 consumers in Greece and WTP was elicited using the contingent valuation method (CVM). Our results show that the majority of Greek consumers are not willing to pay a premium for an insect-based energy bar and cookie (direct entomophagy) and they would require a discount to acquire such products. On the other hand, consumer acceptance is higher for a gilt-head bream that is fed with insect-based feed (indirect entomophagy). Results show that younger adults, indirect consumption of insects, looking for new sources of food and evaluating certification and trust as important for innovative products, are all associated with a higher WTP. Consumers with positive WTP are on average willing to pay a premium of 15.8, 17, and 31.8 per cent for the energy bar, cookie, and gilt-head bream, respectively, while consumers that are not WTP a premium would require discounts of 43.8, 42.4, and 30.7 per cent, respectively.